Fundamentals and application engineering of electrochemical capacitors applications - McDonald, John D. (IEEE, 2010)
This tutorial is targeted at technologists interested in advancing and/or exploiting electrochemical capacitor technology. The fundamentals part of the lecture covers the nature and significance of electric double layer and "pseudocapacitance" charge storage and compares and contrasts these charge storage mechanisms with traditional capacitor and battery technologies. Basic design rules for electrochemical capacitor components are covered including power/energy, Ragone relation, and parameter characterization. In addition, electrochemical capacitors will be compared and contrasted with the properties and performance of electrostatic and electrolytic capacitors, as well as with those of several battery technologies. The fundamentals part will conclude with the present status of electrochemical capacitor technology, available commercial and near-commercial products, manufacturers of these products, and projections of future performance levels. The application engineering part of the lecture provides a systems engineering perspective on the use of ultracapacitors in various industrial, utility or transportation installations. These are illustrated with case studies to expand on the materials presented. Case studies included are representative of the uninterruptible power supply, UPS, material handling such as gantry cranes, heavy industrial equipment such as excavators, telecommunications and transportation areas